The Evaluation of Internet Addiction on Physical Activity and Weight Status among Adolescents in Kuala Lumpur - Hashim, Hani Shifaa Mohd (Universiti Sains Malaysia, 2016)
The purpose of this study was to evaluate the level of internet addiction in relation to physical activity and weight status among adolescents in Kuala Lumpur. A cross-sectional survey was carried out by using a multistage sampling approach, 121 number of adolescents were recruited from five secondary schools in Kuala Lumpur. Their body weight and height were taken and calculated for body mass index (BMI), their physical activity level was measured by using Physical Activity Questionnaire for Adolescents (PAQ-A). Barriers to physical activity was assessed by using domain barriers in International Physical Activity and Network (IPEN) questionnaire. Half of the respondents were given accelerometer GT3X-BT to measure their steps. The level of internet addiction was measured by using Malay Version of Internet Addiction Test (MVIAT). Mean age of respondent was ±15.85 and mean BMI was 22.2 Kg/m2 Out of . 121 numbers of respondent 27.4% was overweight, 69.4% was normal and 4.2% was underweight. As for physical activity, 3.3% of the respondent were classified as active and 58.7% were classified as inactive by using PAQ-A. While when using accelerometer 76.7% of the respondents were classified as inactive and 23% of the respondents were classified as active. Only 0.8% of the respondents were classified as excessive internet users, 15. 7% as moderate users and 83.5% were low users of internet. There are a significant correlation between level of internet addiction and reduced physical activity level,